2019
DOI: 10.1021/acs.orglett.9b03948
|View full text |Cite
|
Sign up to set email alerts
|

Pd(0)-Catalyzed Intramolecular “Ylide-Ullmann-Type” Cyclization of Carbonyl-Stabilized Phosphonium Ylides and Access to Phosphachromones by Exocyclic P–C Cleavage

Abstract: An unprecedented palladium-catalyzed intramolecular Ullmann-type cyclization of carbonyl-stabilized phosphonium ylides with aryl bromides was successfully developed. Furthermore, a base-promoted chemoselective hydrolysis of exocyclic P–C bond of the corresponding phosphonium salts delivered various phosphachromones. Excellent selectivity and high efficiency and good functional group tolerance were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 82 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…The treatment of 3 with BF 3 ·OEt 2 (1 equiv) afforded the phosphonium salt 7 in quantitative yield, the structure of which was determined to be tetrahedral by X-ray crystallographic analysis (see the Supporting Information). When the fluorophosphorane 3 was treated with a few drops of H 2 O, the dibenzophosphole oxide 8aa was formed quantitatively via the loss of pentafluorobenzene 9 . In contrast, the fluorophosphorane 5 afforded the biphenylphosphosphine oxide 10 (54%) upon treatment with H 2 O, with an endocyclic C­(fluoroaryl)–P bond being protonated, and only trace amounts of the corresponding dibenzophosphole 8ca were formed (Scheme b, cf.…”
mentioning
confidence: 99%
“…The treatment of 3 with BF 3 ·OEt 2 (1 equiv) afforded the phosphonium salt 7 in quantitative yield, the structure of which was determined to be tetrahedral by X-ray crystallographic analysis (see the Supporting Information). When the fluorophosphorane 3 was treated with a few drops of H 2 O, the dibenzophosphole oxide 8aa was formed quantitatively via the loss of pentafluorobenzene 9 . In contrast, the fluorophosphorane 5 afforded the biphenylphosphosphine oxide 10 (54%) upon treatment with H 2 O, with an endocyclic C­(fluoroaryl)–P bond being protonated, and only trace amounts of the corresponding dibenzophosphole 8ca were formed (Scheme b, cf.…”
mentioning
confidence: 99%
“…[25] Interestingly, Xu et al reported that the Pd-catalysed intramolecular cyclization of related carbonyl-stabilized phosphonium ylides proceed through Ullman-type O-arylation. [26] With our phosphonium, the use of various Pd catalysts (Pd-(PPh 3 ) 4 , PdCl 2 (PPh 3 ) 2 , Pd(OAc) 2 etc.) did not change the rate of the reaction and only the λ 5 -phosphaacenaphthylene 5 a was formed in similar yields.…”
Section: Resultsmentioning
confidence: 99%
“…[22] Interestingly, Xu et al reported that the Pdcatalysed intramolecular cyclization of related carbonyl-stabilized phosphonium ylides proceed through Ullman-type O-arylation. [23] With our phosphonium, the use of various Pd catalysts (Pd(PPh3)4, PdCl2(PPh3)2, Pd(OAc)2 etc) did not change the fate of the reaction and only the  5phosphaacenaphthylene 5a was formed in similar yields.…”
mentioning
confidence: 80%